2013
DOI: 10.1002/glia.22446
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive 3D cell culture system minimizes cellular stress and maintains the in vivo‐like morphological complexity of astroglial cells

Abstract: We tested the hypothesis that astrocytes grown in a suitable three-dimensional (3D) cell culture system exhibit morphological and biochemical features of in vivo astrocytes that are otherwise lost upon transfer from the in vivo to a two-dimensional (2D) culture environment. First, we report development of a novel bioactively coated nanofiber-based 3D culture system (Bioactive3D) that supports cultures of primary mouse astrocytes. Second, we show that Bioactive3D culture system maintains the in vivo-like morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 29 publications
11
113
1
Order By: Relevance
“…In contrast, GFAP staining in B27 revealed thin and long astrocytes processes. ACM cultures maintained a highly branched and complex phenotype, similar to mature astrocytes observed in vivo 31 .…”
Section: Cell Survival and Morphology In The Long -Term Cultures Figumentioning
confidence: 61%
See 1 more Smart Citation
“…In contrast, GFAP staining in B27 revealed thin and long astrocytes processes. ACM cultures maintained a highly branched and complex phenotype, similar to mature astrocytes observed in vivo 31 .…”
Section: Cell Survival and Morphology In The Long -Term Cultures Figumentioning
confidence: 61%
“…Even though little is known about the in vivo morphology of axonal and dendritic growth cones, some works report evidence that the structure of neuronal growth cones is elaborated with numerous filopodia, especially at early developmental stages 33 . Astrocytes grown in serum -free conditions show a complex morphology that better represents in vivo systems 31,34 comparing to the flat astrocytic cell's bodies observed in FBS (compare astrocytes morphology between ACM and FBS in Fig.3 and Supplementary Fig.3). Indeed, the fibroblast-like morphology of astrocytes is known as an artifact due to the presence of serum in the culturing medium 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Such cultures take longer to become confluent and whilst they too express high levels of GLAST; GLT-1 levels decrease over time, with the functional burden of glutamate transport assumed by GLAST [48,50]. Indeed, research has shown that GLAST mediates the majority of L-glutamate uptake in postnatal cortical astrocyte cultures (28)(29)(30)(31)(32)(33)(34)(35), correlating with increased cell surface expression of GLAST [22].…”
Section: Discussionmentioning
confidence: 99%
“…Scaffolds have been used to recreate aspects of the 3 dimensional arrangement of astrocytes in vitro, for example using collagen [26,27], hydrogels [12,28], tripalmitin [29] and poly-ε-caprolactone electrospun scaffolds [28,30,31]. In this study, we report the use of Alvetex, a commercially available porous scaffold formed of polystyrene that is supplied as cell culture inserts of 200µm thickness [32].…”
Section: Introductionmentioning
confidence: 99%
“…S1). Traditional approaches to study astrocyte-neuron interactions include re-aggregating brain cultures, more defined co-cultures in 2D (Garwood et al 2011;Sandstrom von Tobel et al 2014), or 3D formats (Puschmann et al 2013). An added benefit of defined co-cultures is that human neurons can be studied.…”
Section: Introductionmentioning
confidence: 99%